Esketamine Nasal Spray for the Rapid Reduction of Depressive Symptoms in Major Depressive Disorder With Acute Suicidal Ideation or Behavior. Issue 5 (September 2021) - Canuso, Carla M.; Ionescu, Dawn F.; Li, Xiang; Qiu, Xin; Lane, Rosanne; Turkoz, Ibrahim; Nash, Abigail I.; Lopena, Tricia J.; Fu, Dong-Jing
Abstract: Purpose/Background: Numerous health authority approvals of esketamine nasal spray, combined with oral antidepressant, to treat depressive symptoms in adults with major depressive disorder and acute suicidal ideation or behavior were based on 2 identically designed, double-blind, phase 3 studies. Methods/Procedures: Across both ASPIRE studies (NCT03039192, NCT03097133), patients (N = 456) were randomized to esketamine 84 mg or placebo nasal spray twice weekly for 4 weeks plus comprehensive standard of care, including hospitalization and newly initiated or optimized antidepressant(s). In post hoc analyses of pooled data, changes from baseline at 24 hours after the first dose in Montgomery-Åsberg Depression Rating Scale total score and Clinical Global Impression–Severity of Suicidality–Revised, in the full cohort and in subgroups, were analyzed using analysis of covariance. Findings/Results: Esketamine plus standard of care demonstrated significantly greater improvement in Montgomery-Åsberg Depression Rating Scale total score versus placebo plus standard of care at 24 hours (least square mean difference [95% confidence interval], −3.8 [−5.75 to −1.89]) and at earlier (4 hours: −3.4 [−5.05 to −1.71]) and later time points (day 25: −3.4 [−5.36 to −1.36]). The between-group difference (95% confidence interval) for change in Clinical Global Impression–Severity of Suicidality–Revised at 24 hours was −0.20 (−0.43 to 0.04) for all patients and −0.31 (−0.61 to −0.01) for those with a history of suicide attempt. Common adverse events (≥20%) during esketamine treatment were dizziness, dissociation, nausea, somnolence, and headache. Implications/Conclusions: Esketamine plus comprehensive standard of care rapidly reduces depressive symptoms in patients with major depressive disorder who have acute suicidal ideation or behavior, especially in those with a history of suicide attempt, providing a new treatment option for this particularly ill and vulnerable population. Abstract : Supplemental digital content is available in the text.